Strategi Pengelolaan Agroturism Sebagai Sumber Pendapatan Petani di Desa Rurukan 1 - Christine P.E Porajow; Martinus Sony Erstiawan (CV. Ulil Albab Corp, 2024)
This research aims to determine the development of agrotourism in Rurukan village by identifying a series of potentials, management efforts and participation from all elements of society as well as policies and programs from the government regarding agrotourism, which later from these field data will produce an effective agrotourism development strategy in accordance with local wisdom in Rurukan village, especially for farmers as key stakeholders in developing the agrotourism concept.This research involved farmer respondents and the Rurukan village government using a structured interview data collection method and using SWOT analysis to identify Strengths, Weaknesses, Opportunities and Threats, which was then followed by a SWOT matrix as the final result. in the form of a strategy that can be applied in management. The results of this research found that Minahasa ethnic farmers generally have the characteristics of high independence in managing their business, although in operations the mapalus tradition still strongly binds the social life of the community. So an effective strategy obtained from this research is an agrotourism model management strategy that adapts to local wisdom and the cultural characteristics of farmers in managing agricultural businesses independently in the form of tourismpreneur.